Dayak Values-Based Cognitive Behavioral Therapy for Enhancing Technological Adaptability - Safithry, Esty Aryani (Universitas Negeri Surabaya, 2026)
Background: Rapid digital transformation demands strong psychological adaptability, as difficulties in adjusting to technological change increase vulnerability to stress and reduced well-being. Cognitive Behavioral Therapy (CBT) integrated with Dayak cultural values offers a culturally grounded approach to strengthening adaptive cognition. Objective: This study examined the effectiveness of Dayak Values– Based CBT in enhancing technological adaptability and tested the moderating role of digital literacy. Method: A quasi-experimental 2×2 factorial design was conducted with 80 undergraduate students in Palangkaraya, Indonesia. Participants were grouped based on intervention type (Dayak Values–Based CBT vs. lecture-based instruction) and digital literacy level (high vs. low). Data were analyzed using two-way ANOVA (α = 0.05). Results: Significant main effects of Dayak Values–Based CBT and digital literacy on technological adaptability were found (p < 0.001). No significant interaction effect was observed, indicating consistent intervention effectiveness across literacy levels. Conclusion: Dayak Values–Based CBT effectively enhances technological adaptability through culturally grounded adaptive thinking and supports the development of culturally responsive psychological interventions in the digital era. Abstrak Latar Belakang: Transformasi digital secara pesat menuntut adaptabilitas psikologis yang kuat, karena kesulitan dalam menyesuaikan diri dengan perubahan teknologi meningkatkan kerentanan terhadap stres dan penurunan kesejahteraan. Terapi Perilaku Kognitif (CBT) yang terintegrasi dengan nilai-nilai budaya Dayak menawarkan pendekatan yang berlandaskan budaya untuk memperkuat kognisi adaptif. Tujuan: Studi ini meneliti efektivitas CBT Berbasis Nilai Dayak dalam meningkatkan adaptabilitas teknologi dan menguji peran moderasi literasi digital. Metode: Desain faktorial 2×2 kuasi-eksperimental dilakukan dengan 80 mahasiswa S1 di Palangkaraya, Indonesia. Partisipan dikelompokkan berdasarkan jenis intervensi (CBT Berbasis Nilai Dayak vs. instruksi berbasis ceramah) dan tingkat literasi digital (tinggi vs. rendah). Data dianalisis menggunakan ANOVA dua arah (α = 0,05). Hasil: Ditemukan efek utama yang signifikan dari CBT Berbasis Nilai Dayak dan literasi digital terhadap adaptabilitas teknologi (p < 0,001). Tidak ditemukan efek interaksi yang signifikan, menunjukkan efektivitas intervensi yang konsisten di berbagai tingkat literasi. Kesimpulan: Terapi Perilaku Kognitif Berbasis Nilai-Nilai Dayak secara efektif meningkatkan kemampuan beradaptasi terhadap teknologi melalui pemikiran adaptif yang berlandaskan budaya dan mendukung pengembangan intervensi psikologis yang responsif secara budaya di era digital.